Indefeasibility of Title and Its Protective Limits in the Contemporary Torrens System - Velliana Samudro; Rasji Rasji (Jurnal Ilmu Hukum Kyadiren, 2026)
Legal certainty in land rights constitutes a fundamental objective of modern land registration systems, including those based on the Torrens system through the application of the principle of indefeasibility of title. This study examines the regulation of the principle of indefeasibility of title under the Land Title Act 2000 of the Northern Territory, analyzes the nature and legal foundations of its exceptions, and evaluates its implications for the protection and certainty of land rights. The research employs a normative legal methodology utilizing statutory, conceptual, and comparative approaches. Legal materials are analyzed qualitatively through a comprehensive review of relevant legislation, legal doctrines, and scholarly literature. The findings demonstrate that the Land Title Act 2000 adopts a model of qualified indefeasibility, which affords strong protection to registered proprietors while recognizing limited statutory exceptions under Section 198 to preserve a balance between legal certainty and substantive justice. The implementation of this principle, reinforced by the mirror, curtain, and insurance principles, enhances transaction security, minimizes land disputes, and strengthens public confidence in the land registration system. Accordingly, the qualified indefeasibility model effectively promotes legal certainty while safeguarding substantive justice within the contemporary Torrens system.